Survival analysis of timing of first marriage among women of reproductive age in Nigeria: Regional differences (2012)
Early marriage is common among women in developing countries. Age at first marriage (AFM) has health implication on women and their under-five children. In Nigeria, few studies have explored AFM; the current study was designed to fill the gap. Nigeria Demographic and Health Survey, 2008 dataset on married women aged 15-49(N=24,986) was used. Chi-square, OLS regression and Cox proportional hazard models were used in the analysis. The mean AFM was 17.8±4.8 years and significant difference existed between the mean AFM of women in the North (16.0±3.6) and South (20.4±5.0) (p<0.001). Region, education, religion, residence, nutritional status, age at first sexual intercourse and children ever born were significantly associated with timing of first marriage (p<0.001). Majority of the women married between ages 15-19 years (43.1%), while very few married late (2.3%) and about 27.0% married too early (less than 15years). Early marriage was more common in all the regions in the North than the South and the hazard was highest in the North West and North East. Women who reside in rural area (H.R=1.15; C.I=1.111.18) married early than their counterparts in the urban area. Age at first marriage was directly related to levels of education (p<0.001). Muslim women married early (H.R=1.34; C.I=1.29 1.39) than Christians. Three models were generated from the data. Women married too early in Nigeria with Teenage marriage more common in the North than the South. Education has influence on AFM; therefore, women should have at least secondary education before marriage in Nigeria.